The Politics of Aging and Retirement: Evidence from Swiss Referenda - Piera Bello; Vincenzo Galasso (Center for Economic Studies and ifo Institute (CESifo), 2018)
Aging creates financial troubles for PAYG pension systems, since the share of retirees to workers increases. An often advocated policy response is to increase retirement age. Ironically, however, the political support for this policy may actually be hindered by population aging. Using Swiss administrative voting data at municipal level (and individual survey data) from pension reforms referenda, we show in fact that individuals close to retirement tend to oppose policies that postpone retirement, whereas young and elderly individuals are more favorable. The current process of population aging, and the associated increase in the size of the cohort of individuals close to retirement, may partially explain why a pension reform, which increased retirement age for females, was approved in two referenda in 1995 and 1998, while a reform, which proposed a similar increase in female retirement age, was defeated in a 2017 referendum.
Keywords: H55; D72; J18; 330; social security reforms; voting behavior; retirement age